2012
DOI: 10.1099/vir.0.041053-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection and pathogenesis of Huaiyangshan virus (a novel tick-borne bunyavirus) in laboratory rodents

Abstract: A novel tick-borne bunyavirus (Huaiyangshan virus, HYSV), which causes haemorrhagic fever-like disease, has recently been reported in China. So far no animal experiments have been performed to study its pathogenesis. Towards developing an animal model for HYSV fever, newborn and adult mice and rats and golden hamsters were inoculated intracerebrally or intraperitoneally with HYSV. Newborn rats and newborn mice, especially Kunming (KM) mice, appeared highly susceptible. Remarkably, the KM mice that died of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 18 publications
2
73
0
Order By: Relevance
“…A previous study showed that all newborn mice of the Kungming (KM), BALB/c, and C57/BL6 strains died after intracerebral inoculation of SFTSV, while 35 to 50% of newborn mice died after intraperitoneal inoculation of SFTSV (10). However, we demonstrated that newborn CD-1 mice developed signs of illness (lethargy, tremors, and loss of balance) beginning 7 to 8 days p.i., but no mouse died of SFTSV infection.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…A previous study showed that all newborn mice of the Kungming (KM), BALB/c, and C57/BL6 strains died after intracerebral inoculation of SFTSV, while 35 to 50% of newborn mice died after intraperitoneal inoculation of SFTSV (10). However, we demonstrated that newborn CD-1 mice developed signs of illness (lethargy, tremors, and loss of balance) beginning 7 to 8 days p.i., but no mouse died of SFTSV infection.…”
Section: Discussionmentioning
confidence: 52%
“…The difference in the susceptibility of the mice to SFTSV may be caused by genetic differences in the mice. Previous studies demonstrated that adult mice of the KM, BALB/c, and C57/BL6 strains are not susceptible to SFTSV regardless of the inoculation route (9,10). The only signs of SFTSV infection in C57/BL6 mice are slightly low white blood cell and platelet counts at one time point (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…or intraperitoneally (i.p) with SFTSV supernatant, and the result showed that all newborn rats and mice were died from i.c. challenge, while 35~50% of newborn mice died from i.p., and no significant clinical manifestation was observed in all adult animals [31]. Hallmark symptoms of thrombocytopenia and leukocytopenia were obtained in C57/BL6 mice through intramuscular inoculation of SFTSV, and if the SFTSVinfected mice were pretreated with immunosuppressive drug mitomycin C, 50% of them would die between day 9 and day 10, and the remaining surviving mice experienced a significant loss of body mass compared with uninfected mice administered mitomycin C in parallel [32].…”
Section: Animal Infection Modelmentioning
confidence: 97%